FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Khairani, Permata; Prihatni, Rida; Yusuf, Muhammad (Cahaya Ilmu Bangsa, 2025)
This research aims to analyze the effect of managerial ownership, institutional ownership, leverage, accounting conservatism, and tax planning on earnings management. This research uses a quantitative method with a unit of analysis of companies listed on the Indonesia Stock Exchange. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange for the period 2022 - 2023. The samples were 52 companies, the selection used Non-Probability Sampling method with purposive sampling technique. This research uses multiple regression methods to investigate the relationship between each independent variable on earnings management and uses of Eviews 12. The results of this research indicate that leverage and accounting conservatism affect earnings management. Meanwhile, managerial ownership, institutional ownership, and tax planning have no effect on earnings management.